Tackling Food Insecurity in Cabo Verde Islands: The Nutritional, Agricultural and Environmental Values of the Legume Species - Brilhante, Miguel (Foods, 2021)
Legume species are important food sources to reduce hunger and deal with malnutrition; they also play a crucial role in sustainable agriculture in the tropical dry islands of Cabo Verde. To improve the knowledge of the heritage of plant genetic resources in this Middle Income Country, this study had three main goals: (i) to provide a checklist of food legumes; (ii) to investigate which species are traded in local markets and, based on field surveys, to compare species for their chemical, phenolic, antioxidant, and nutritional composition; and (iii) to discuss the agronomic value and contribution to food security in this archipelago. Our results revealed that 15 species are used as food and 5 of them are locally traded (Cajanus cajan, Lablab purpureus, Phaseolus lunatus, Phaseolus vulgaris, and Vigna unguiculata). The role of these species as sources of important minerals, antioxidants, and nutritional components for food security is highlighted, and the native ones (Lablab purpureus and Vigna unguiculata) stand-out as particularly well-adapted to the climate of these islands, which are already experiencing the adverse effects of climate change. We conclude that the sustainable use of these genetic resources can contribute to the reduction of hunger and poverty, thus meeting some challenges of the Sustainable Development Goals.